Pengaruh Budaya Organisasi dan Kepemimpinan Transformasional Terhadap Kinerja Karyawan dengan Motivasi Kerja sebagai Variabel Intervening pada UMKM di Desa Padurenan - Fadlli, Amin; Widjajanti, Kesi; Santoso, Djoko (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2023)
This research is motivated by the existence of a problem that has not achieved optimal employee performance in accordance with the abilities and competency standards that have been set so that they cannot meet the work targets that have been set. This study aims to analyze the influence of organizational culture and transformational leadership on employee performance with work motivation as an intervening variable.This study uses a quantitative approach. The population in this study were 85 respondents. The sample used is purposive sampling technique. The type of data used is primary data. Data collection techniques using a questionnaire. The data analysis technique used is multiple linear regression analysis technique.The conclusion of this study is that organizational culture has a positive and significant effect on work motivation. transformational leadership has a positive and significant effect on work motivation. organizational culture has a positive and significant effect on employee performance. transformational leadership has a positive and significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Work motivation is able to mediate organizational culture and transformational leadership on employee performance.